Arteria – A Regional Cultural Mapping Project in Portugal - Veronnezzi Pacheco, João Luís; Carvalho, Claudia Pato (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2015)
This paper discusses the relation between cultural mapping and participatory community cultural mapping, proposing the integration of a mobile device application (app) in the cultural mapping process of the Arteria project. This application aims to expand the notion of cultural appropriation by exploring how citizens can make crucial contributions to the cultural mapping process. This technology will evolve from and improve Arteria’s digital platform/website by boosting the processes of collection and registration of tangible and intangible cultural assets and the dissemination of registered cultural assets. The app will also enhance the connection among socio-cultural actors and improve the quality of community involvement in the cultural, social, and political dynamics of this cultural mapping project. To justify the need for such a tool, an overview of the project’s intent, objectives, and activities is presented, as well as its philosophy of intervention in local communities.